Antecedents and consequences of trust on a virtual team leader - Carlos Flavián Blanco; Miguel Guinalíu; Pau Jordan (European Journal of Management and Business Economics (EJM&BE), 2019)
Purpose: The purpose of this paper is to examine, among the possible causes, whether trust in the leader is one of the most relevant factors on the success of a virtual work team by analyzing different antecedents of the trust and its consequences. Design/methodology/approach: The influence that certain physical and behavioral characteristics of the leader (attractiveness, empathy and justice) exert on the degree of trust is evaluated. On the other hand, the influence of trust on the efficiency of the team, in terms of organizational citizenship behavior and commitment, is analyzed. To test the model, a survey was conducted on real work teams and the data were analyzed through a model of structural equations. Findings: The results support the hypotheses and consequently, the relevance of trust in the leader. Specifically, the leader's physical and behavioral characteristics have a significant effect on the trust in the leader. This trust results in greater organizational efficiency. Originality/value: Despite the undisputable growth in the number of companies using virtual teams, it is also true that many of these teams fail to perform. In this sense, this paper analyzes if certain factors related to leadership can be relevant when influencing the efficiency of a virtual work team. This paper contributes to a better understanding of the internal processes within a virtual team in order to maximize the chances of success in this type of organizations.
Keywords: 650; Leadership; Trust; Justice; Empathy; Virtual team; Attractive